PERAN MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN KINERJA APARATUR DESA LOMBO KABUPATEN SIDENRENG RAPPANG - Abdul Kadir; Dian Nirmasari (Universitas Ichsan Sidenreng Rappang, 2024)
This research aims to identify the role of human resource management (HRM) in improving the performance of village officials in Lombo Village, Sidenreng Rappang Regency. The research method used is a qualitative approach with descriptive case studies. Primary data was collected through interviews with village government officials, while secondary data was obtained from various sources such as websites, social media, books, and presentation materials. Literature reviews on HRM and performance were used as the basis for data analysis. The research findings indicate that HRM plays a crucial role in enhancing the performance of village officials. Careful selection of village officials involving community participation, employee development through training and education, and providing fair and adequate compensation are some key aspects identified. Based on the research findings, it is recommended to continue improving the selection process of village officials with greater precision and transparency, continuing investment in employee development, implementing periodic and objective performance assessment systems, and reviewing and updating existing compensation systems. It is hoped that the implementation of these recommendations will enhance the effectiveness of HRM at the village level, which in turn will contribute to improving the performance of village officials and village development overall.